PENGARUH IMPLEMENTASI KEBIJAKAN SISTEM INFORMASI PEMBANGUNAN DAERAH TERHADAP MANAJEMEN DATA DAN INFORMASI PEMBANGUNAN DALAM RANGKA MEWUJUDKAN EFEKTIVITAS PERENCANAAN PEMBANGUNAN DAERAH - Siti Asyaroh (Sekolah Tinggi Ilmu Administrasi Sebelas April Sumedang, 2019)
This study was aimed to test and analyze the effects of policy implementation of regional development information system on data and information management of development in enabling effectiveness of regional development planning on Local Government Agencies (SKPD) of Sumedang Regency.Research method used was analytic descriptive with survey technique on independent variable of Effect of Policy Implementation of Regional Development Information System, and dependent variable of Effectiveness of Regional Development Planning on SKPD of Sumedang Regency. The population was 62 people from all of SKPD under Sumedang regency government. Sampling technique used was saturated sampling or census, where entire population were the respondents. Data collection was by document study and field study of observation, questionnaire,and interview.Data analysis technique in this study was path analysis. Testing result of main hypothesis showed that effect of policy implementation of regional development information system (X) on data and information management of regional development (Y) in enabling the effectiveness of regional development planning on SKPD (Z) was 25.5%. Effect of policy implementation of regional development information system (X) on data and information management of regional development (Y) was 16.0%. Effect of policy implementation of regional development information system (X) on effectiveness of regional development planning on SKPD (Z) was 25.2%. And effect of data and information management of regional development (Y) on effectiveness of regional development planning on SKPD (Z) was 27.7%. Result of this study has implication on the effectiveness of regional development planning on SKPD of Sumedang regency, but there are issues need to address.To overcome problems in the implementation of regional development information system, it is recommended to increase number of personnel and improve their competency. As for overcoming the problems in data and information management of development, leaders should encourage data and information management to have better control. And for improvement in effectiveness of regional development planning by SKPD of Sumedang Regency, it is recommended to maintain good items, and to implement programs that promote public selfsupportability, economic equality, and better education.